2012
DOI: 10.1111/j.1538-7836.2011.04554.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of fucoidan‐stimulated endothelial colony‐forming cells in peripheral ischemia

Abstract: Summary. Background: Fucoidan, an antithrombotic polysaccharide, can induce endothelial colony-forming cells (ECFC) to adopt an angiogenic phenotype in vitro. Objectives: We evaluated the effect of fucoidan on vasculogenesis induced by ECFC in vivo. Methods: We used a murine hindlimb ischemia model to probe the synergic role of fucoidan-treatment and ECFC infusion during tissue repair. Results: We found that exposure of ECFC to fucoidan prior to their intravenous injection improved residual muscle blood flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Animal care conformed to French guidelines (Services Vétérinaires de la Santé et de la Production Animale, Paris, France), and experiments were performed in keeping with the guidelines of the Paris-Descartes University Institutional Committee on Animal Care and Use (C75.06.02). The mice underwent surgery to induce unilateral hind limb ischemia as previously described [23,24]. Briefly, animals were anesthetized by inhalation of isoflurane.…”
Section: Murine Model Of Hind Limb Ischemiamentioning
confidence: 99%
“…Animal care conformed to French guidelines (Services Vétérinaires de la Santé et de la Production Animale, Paris, France), and experiments were performed in keeping with the guidelines of the Paris-Descartes University Institutional Committee on Animal Care and Use (C75.06.02). The mice underwent surgery to induce unilateral hind limb ischemia as previously described [23,24]. Briefly, animals were anesthetized by inhalation of isoflurane.…”
Section: Murine Model Of Hind Limb Ischemiamentioning
confidence: 99%
“…Fucoidan may bind proangiogenic growth factors and confer a stable, receptor-compatible conformational change upon growth factors, which might increase their affinity for their receptors and improve the angiogenesis process (Sarlon et al 2012). Competitive binding of fucoidan to SDF-1 promotes its release from the surface of endothelial cells and the extracellular matrix in the bone marrow and other tissues, which results in the mobilization of bone-marrow stem cells (Sweeney et al 2002).…”
Section: Angiogenesis: Modulating the Proangiogenic Factorsmentioning
confidence: 99%
“…This latter effect was correlated with upregulation of the cell-surface a6 integrin subunit of the laminin receptor and the authors suggest that ex vivo fucoidan might precondition EPC and lead to increased neovascularization when injected into ischemic tissues. Sarlon et al (2012) showed that fucoidan greatly increases ECFCmediated angiogenesis in vivo. ECFC stimulation with fucoidan caused a rapid increase in cell adhesion to activated endothelium in flow conditions, and enhanced transendothelial extravasation.…”
Section: Vasculogenesis: Mobilization Of Endothelial Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-molecular-weight fucoidan (LMW-Fuc) extracted from the brown algae Asco­phyllum nodosum was described to present negligible anticoagulant activity, but potent antithrombotic and pro-angiogenic effects, being suggested as potential neovascularization agent [14, 15]. Nevertheless, no studies have addressed the specific effects of LMW-Fuc on the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%